(untitled) (Journal of Scientific Research, 2018)
The methanol, ethanol and chlorofom leaf extracts of Satkara, Citrus assamensis (family: Rutaceae), were subjected to in vitro anti-bacterial, thrombolytic, membrane stabilizing and in vivo anti-inflammatory and antitumor activity tests. The chloroform extract of C. assamensis showed the most important spectrum of activity against Bacillus subtilis, Bacillus cereus, Sarcina lutea among 6 gram positive and against 11 gram negative bacteria at the concentration of 1000 μg/disc, while the range of zones of inhibition were within 7-16 mm. Among the tested three extracts CHCl3 extract showed potent thrombolytic activity and hypotonic solution induced haemolytic activity where the percentages of inhibition were found to be 35% and 55% respectively. All the extracts established significant (p<0.05) anti-inflammatory effect by regulating biphasic inflammatory process induced by carrageenan. The leaf extract dose-dependently and significantly decreases the number of EAC cell count and inhibition of cell growth in comparison to the EAC control and standard. The results obtained in the present study indicate that, C. assamensis leaf can be a potential source of anti-bacterial, thrombolytic, membrane stabilizing, anti-inflammatory and antitumor agents.